2013
DOI: 10.2337/db12-0294
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of GIP in Pancreatic β-Cells Maintains Enhanced Insulin Secretion in Mice With Complete Absence of Proglucagon-Derived Peptides

Abstract: Glucagon and glucagon-like peptide-1 (GLP-1) are produced in pancreatic α-cells and enteroendocrine L-cells, respectively, in a tissue-specific manner from the same precursor, proglucagon, that is encoded by glucagon gene (Gcg), and play critical roles in glucose homeostasis. Here, we studied glucose homeostasis and β-cell function of Gcg-deficient mice that are homozygous for a Gcg-GFP knock-in allele (Gcggfp/gfp). The Gcggfp/gfp mice displayed improved glucose tolerance and enhanced insulin secretion, as ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 35 publications
(59 reference statements)
2
46
0
Order By: Relevance
“…liferation of β cells (Kim et al, 2005). Expression of GIP in pancreatic β cells has been reported by Fukami et al (2013), but the effect of hepatic GIP protein dynamics in diabetes was unclear. In this study, it should be considered that insulin concentration and the condition of pancreatic β cells after STZ treatment might affect the landscape of GIP-diabetes dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…liferation of β cells (Kim et al, 2005). Expression of GIP in pancreatic β cells has been reported by Fukami et al (2013), but the effect of hepatic GIP protein dynamics in diabetes was unclear. In this study, it should be considered that insulin concentration and the condition of pancreatic β cells after STZ treatment might affect the landscape of GIP-diabetes dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…A vast majority of these studies concluded that anti-glucagon strategies improve glucose tolerance and attributed the improvement to a decreased glucagon action. More recent studies using glucagon receptor or glucagon knockout mice showed that other mechanisms might also contribute to the improved glucose tolerance such as a compensatory action of incretins and particularly GLP-1, the levels of which dramatically increased when glucagon action is disrupted (Hayashi 2011;Hayashi et al 2009;Ali et al 2011;Gu et al 2010;Sorensen et al 2006;Fukami et al 2013). Interestingly, metformin, a first-line anti-diabetic agent, has been shown to improve glucose tolerance by suppressing hepatic glucagon signaling via a decreased production of cAMP (Miller et al 2013).…”
Section: Therapies Targeting Glucagon Actionmentioning
confidence: 99%
“…The number of islets and the area they encompass are significantly increased in the Gcg gfp/gfp mice [3], [15]. To address whether functionally defective mutation of ARX influence islet number and area, we performed a histological analysis of the pancreas of Gcg/Arx double mutant mice at 2 weeks of age.…”
Section: Resultsmentioning
confidence: 99%
“…The islet area was determined using slight modifications of the previously described method [13], [14], [15]. In brief, the complete pancreas in the paraffin block was cut into 6 µm sections.…”
Section: Methodsmentioning
confidence: 99%